Analisis impor beras Indonesia - Sani, Yulia; Hodijah, Siti; Rosmeli, Rosmeli (e-Journal Perdagangan Industri dan Moneter, 2020)
This study aims to analyze the development of each variable and its effect on rice imports in Indonesia for the period 1998-2017. This research uses descriptive and quantitative analysis tools. The data used is time-series data or time series. To analyze this research, the "Ordinary Least Square (OLS) method was used. The results showed that the independent variables simultaneously had a significant effect on rice imports in Indonesia. Partially, the domestic rice price variable has a positive and significant effect on rice imports in Indonesia, the exchange rate variable has a negative and significant effect on rice imports in Indonesia and the GDP variable has a negative and significant effect on rice imports in Indonesia. Keywords: Rice imports, Exchange rate, The price of rice